Calcium Imbalance and Hypothyroidism: Exploring the Relationship - Sultana, Sabera; Mosammad Alpana Jahan; Syed Minhaj Uddin Ahmed; Rabeya Sultana; Fatema Ferdous Ara (KYAMC Journal, 2024)
Background: The thyroid gland synthesizes mainly two hormones, triiodothyronine (T3) and thyroxin (T4) which are important to maintain various functions especially metabolic, mineral and thermogenic homeostasis in body. The disorders of thyroid function especially hypothyroidism is important it can cause of disturbance in calcium metabolism by their direct action on bone turnover. Objective: This study was designed to assess the role of hypothyroidism in serum calcium levels. Materials and Methods: This case-control study was done in the Laboratory Service Department, Khwaja Yunus Ali Medical College and Hospital, Enayetpur, Sirajganj from February 2023 to June 2023. A total of 45 subjects of hypothyroidism of both sexes were selected for the purpose. Data were collected in and analysis was done by IBM SPSS Statistics for Windows, version 23.0 (IBM Corp., Armonk, N.Y., USA) software. The categorical variables were represented as percentages and measurable variables as mean ± SD. Pearson’s correlation test was used to observe the correlation of calcium level with other variables. P value ≤ 0.05 was considered to be statistically significant. Results: There is a significant positive correlation of serum T3 & T4 with serum calcium in hypothyroid patients. The r value is +0.73(p value = 0.02). (r value + 0.78and p value < 0.05) respectively. There is strong negative correlation between TSH and serum calcium levels in hypothyroid patients (r value -0.58 and p value0.03). Conclusion: This study result shows, serum calcium levels significantly decrease in hypothyroid patients. Therefore, it is important to check the level of calcium in thyroid disorders. If necessary, the supplementation of mineral should be given in order to prevent further bone complication. KYAMC Journal Volume: 14, No: 04, January 2024: 194-197.